1998
DOI: 10.1002/(sici)1097-0274(199812)34:6<529::aid-ajim1>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Occupational respiratory allergy in bakery workers: A review of the literature

Abstract: Baker's asthma has long been recognized as a serious disease among workers in the bakery industry and the number of cases with baker's asthma is steadily increasing. This paper presents a review of the available literature on baker's allergy with a special focus on the allergens involved, the epidemiologic research and issues on exposure assessment, evidence of exposure‐response‐relationships, and possible prevention strategies. A large number of potential allergens have been identified and are described here.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 0 publications
2
55
0
2
Order By: Relevance
“…Several studies have demonstrated a wide variety of time-weighted dust loads in bakeries, ranging from about 1 up to 10 mg/m 3 [9,13,24,25]. The highest load can be found during doughmaking and breadforming.…”
Section: Causative Dust and Airborne Allergen Loads In Bakeriesmentioning
confidence: 99%
“…Several studies have demonstrated a wide variety of time-weighted dust loads in bakeries, ranging from about 1 up to 10 mg/m 3 [9,13,24,25]. The highest load can be found during doughmaking and breadforming.…”
Section: Causative Dust and Airborne Allergen Loads In Bakeriesmentioning
confidence: 99%
“…The respiratory morbidity is partly due to allergic, IgE-mediated sensitization to¯our proteins and additives. In cross-sectional studies, 29±50% of rhinitic bakers were sensitized to occupational allergens [6,10,22], whereas in a longitudinal study, only 2 of 45 bakers with work-related rhinoconjunctivitis with onset during the ®rst 4 years of bakery work were sensitized to¯our [5]. Thus, nonallergic mechanisms are also likely to be involved in respiratory tract disease among bakers.…”
Section: Introductionmentioning
confidence: 99%
“…For wheat¯our, however, there is no clear standard. If wheat¯our is considered a``nuisance dust'', a possible reference limit value could be 10 mg/m 3 as the TLV-TWA, a ®gure seldom exceeded in bakeries and¯our mills [5]. The few data available about airborne¯our-dust levels during challenge show that only with recently developed close-circuit devices is it possible to keep the concentration of inhaled particles low and relatively constant [1,7].…”
Section: Discussionmentioning
confidence: 99%